Analisis Hukum Kekuatan Pembuktian Akta Autentik Notaris yang Terdegrasi - Intan Novitasari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The need for legal certainty in society is reflected in the increasing number of agreements executed in the form of authentic deeds prepared by Notaries. The presence of Notaries as public officials or public officers serves as a response to every citizen’s need for legal certainty. Such legal certainty is manifested through contractual documents in the form of Notarial Deeds, which possess authentic status and full evidentiary force. However, when a Notary commits violations in carrying out their duties and authority, the deed may experience a degradation of its evidentiary value, resulting in its status being reduced to that of a private deed or even being declared null and void by law. This study employs a normative legal research method with a descriptive approach, aiming to analyze the causes of the degradation of the evidentiary value of Notarial Deeds and its legal consequences for the protection of civil rights. The degradation of the evidentiary value of authentic deeds may occur due to violations of formal requirements in the process of preparing the deed. Such violations continue to occur in practice, indicating vulnerabilities in the performance of Notaries’ duties and offices and potentially affecting legal certainty and legal protection for the parties concerned.